Quality Improvement in Behavioral Health - O'Donohue, William; Maragakis, Alexandros (Springer International Publishing : Imprint: Springer, 2016)
This innovative volume presents a cogent case for quality improvement (QI) in behavioral healthcare as ethical practice, solid science, and good business. Divided between foundational concepts, key QI tools and methods, and emerging applications, it offers guidelines for raising care standards while addressing ongoing issues of treatment validity, staffing and training, costs and funding, and integration with medical systems. Expert contributors review the implications and potential of QI in diverse areas such as treatment of entrenched mental disorders, in correctional facilities, and within the professional context of the American Psychological Association. The insights, examples, and strategies featured will increase in value as behavioral health becomes more prominent in integrated care and vital to large-scale health goals. Included in the coverage: Behavioral health conditions: direct treatment costs and indirect social costs. Quality improvement and clinical psychological science. Process mapping to improve quality in behavioral health service delivery. · Checklists for quality improvement and evaluation in behavioral health. · Creating a quality improvement system for an integrated care program: the why, what, and how to measu re. · Feedback Informed Treatment (FIT): improving the outcome of psychotherapy one person at a time. Qualit y Improvement in Behavioral Healthcare gives health psychologists, public health professionals, and health administrators a real-world framework for maintaining quality services in a rapidly evolving health landscape. .